2014
DOI: 10.1039/c4dt00152d
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and catalytic activity of tert-butoxy-aluminium hydride reagents

Abstract: The reactivity and catalytic activities of the tert-butoxy aluminium hydride reagents [((t)BuO)xAlH3-x] [x = 1 (1), 2 (2)] and (L)Li[((t)BuO)2AlH2] [L = THF (3), 1,4-dioxane (4)] are investigated. The structural characterisation of the novel compounds 3 and 4 shows that the nature of the hydridic species present is affected dramatically by the donor ligand coordinating the Li(+) cation. Stoichiometric reaction of 1 with pyridine gives [(1,4-H-pyrid-1-yl)4Al](-)[(pyridine)4AlH2](+) (5) while reaction with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…For example, 10 mol % of LiAlH 4 converted Me 2 NH⋅BH 3 almost quantitatively to dimeric (Me 2 NBH 2 ) 2 when refluxed in toluene for 16 hours . Similarly, neutral [( t BuO) x AlH 3− x ] ( x= 1 or 2) and lithium salts of [( t BuO) 2 AlH 2 ] − were found to catalyze the dehydrogenation of Me 2 NH⋅BH 3 , with [ t BuO 2 AlH 2 ] − being superior compared with the other tert ‐butoxy‐substituted aluminum catalysts . Nonetheless, the underlying mechanism for dehydrogenation of amine–boranes is much more complicated and still needs further investigations.…”
Section: Acid and Base‐catalyzed Dehydrogenationmentioning
confidence: 99%
“…For example, 10 mol % of LiAlH 4 converted Me 2 NH⋅BH 3 almost quantitatively to dimeric (Me 2 NBH 2 ) 2 when refluxed in toluene for 16 hours . Similarly, neutral [( t BuO) x AlH 3− x ] ( x= 1 or 2) and lithium salts of [( t BuO) 2 AlH 2 ] − were found to catalyze the dehydrogenation of Me 2 NH⋅BH 3 , with [ t BuO 2 AlH 2 ] − being superior compared with the other tert ‐butoxy‐substituted aluminum catalysts . Nonetheless, the underlying mechanism for dehydrogenation of amine–boranes is much more complicated and still needs further investigations.…”
Section: Acid and Base‐catalyzed Dehydrogenationmentioning
confidence: 99%
“…26 Replacement of Al III by Ga III was interesting given their identical formal charges and similarity of their radii (due to the d-block contraction) thereby offering potentially similar Lewis acidity. 26 Replacement of Al III by Ga III was interesting given their identical formal charges and similarity of their radii (due to the d-block contraction) thereby offering potentially similar Lewis acidity.…”
Section: View Article Onlinementioning
confidence: 99%
“…96[AlH 4 ]) [113] was isolated( 17 %, Figure 28). [115] Recently,o ur group has discovered that the conversion of the bis(imino) diboron(II) dications alt 60[SbCl 6 ] 2 with an excess of Li[AlH 4 ]r esults in ligand transfer between the two Group 13 metals to produce the bis(imino) aluminum dihydride cation salt 61[AlB 2 H 8 ] ( Figure 17 and Figure 28). [68] With regard to the structural parameters of the ligand scaffold, the XRD study of the complex cation revealed CÀN imino bond lengths of 1.330(2) and 1.329(2) ,w hich is slightly longer than in the lighter boron homologue 30 + (Figure 10, 1.317(5), 1.318(4) ).…”
Section: Aluminum Cationswith N-donor Anchor Ligandsmentioning
confidence: 99%
“…More recently,L ess, Simmonds and Wright converted (tBuOAlH 2 ) 2 with an excess of pyridine and crystallized [(pyridine) 4 AlH 2 ][Al(NC 5 H 6 ) 4 ]i nl ow yield (18 %). [115] The compound marks as ix-coordinate aluminum complex cation and af ourcoordinate metal complexa nion.T he [AlH 2 ] + fragment in the former is thermodynamically stabilized by the four N-donor atoms of the pyridine ligands, whereas in the latter,t he aluminum atom is bonded to four formally anionic 4-H-pyridyl groups that presumably result from hydride transfer to pyridine. To elucidate the mechanism of the dehydrocoupling of Figure 27.…”
mentioning
confidence: 99%